Stick the face out. Talking Head's use in online courses - Riccardo Fattorini; Gisella Paoletti (Firenze University Press, 2017)
In this essay we intend to examine in which contexts and under which conditions a particular and common video format that has within it a Talking Head of the speaker may be an opportunity in teaching or vice versa a critical issue. We will pay particular attention to the use of gestures and the connection between gestures and spoken word; because, gesture and speech form a set that can be significant and lead to understanding the lesson, learning and motivation of the student, but can also represent sources of cognitive load. We will propose the distinction, in the analysis, of significant/insignificant multimedia gestures as one of the elements that help to evaluate the potential of an educational event.   Mettiamoci la faccia. L'uso dei Talking Head nelle lezioni online In questo saggio intendiamo esaminare in quali contesti e a quali condizioni un particolare e diffuso formato di video che presenta al suo interno un Talking Head del parlante può rappresentare una opportunità nell'insegnamento o viceversa una criticità. Presteremo particolare attenzione all'uso dei gesti e al collegamento tra gesti e discorso parlato, in quanto gesto e discorso formano un insieme che può essere significativo e aiutare la comprensione della lezione, l'apprendimento e la motivazione dello studente, ma possono rappresentare anche fonti di carico cognitivo. Proporremo una distinzione, nell'analisi, tra gesti significativi/non significativi come uno degli elementi che aiutano a valutare le potenzialità di un evento educativo di tipo multimediale.